Development of AVooks (Audio-Visual Books) Based on the Flipped Classroom Model to Enhance Learning Independence and Self-Efficacy among Students with Physical Disabilities - Venissa Dian Mawarsari; Martyana Prihaswati; Eko Andy Purnomo; Abdul Aziz; Iswahyudi Joko Suprayitno (Universitas Muhammadiyah Sumatera Utara, 2026)
This study aimed to develop and evaluate the effectiveness of AVooks (Audio-Visual Books) based on the flipped classroom model in enhancing the learning independence and self-efficacy of university students with physical disabilities in the Multimedia Mathematics Learning course. AVooks is an accessibility-oriented learning medium that integrates text, audio narration, visual tutorials, and interactive navigation within a Learning Management System (LMS), enabling students to learn independently according to their individual learning pace and physical conditions. This study employed a Research and Development (R&D) approach using the ADDIE model. The participants were two university students with physical disabilities characterized by upper- and lower-limb deformities who were able to walk independently without using wheelchairs or other mobility aids. Data were collected using validated learning independence and self-efficacy questionnaires administered over seven learning sessions and analyzed using descriptive analysis, Achievement Percentage, and Normalized Gain (N-Gain). Expert validation indicated that AVooks was highly feasible for implementation, with an average score of 3.56. The results showed that the Achievement Percentage of learning independence increased from 45.00% to 91.60%, with an N-Gain score of 0.85 (high category). Likewise, the Achievement Percentage of self-efficacy increased from 41.60% to 93.40%, with an N-Gain score of 0.89 (high category). These findings indicate that integrating AVooks with the flipped classroom model provides an accessible and adaptive learning environment that effectively promotes learning independence and strengthens students' confidence in completing academic tasks. This study contributes to the advancement of inclusive higher education by demonstrating the potential of accessibility-oriented digital learning media to support university students with physical disabilities.